2015
DOI: 10.3390/w7062622
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Mulch and Irrigation Amount on Soil Water Distribution and Root Zone Water Balance Using HYDRUS-2D

Abstract: Water scarcity is the most critical constraint for sustainable cotton production in Xinjiang Province, northwest China. Drip irrigation under mulch is a major water-saving irrigation method that has been widely practiced for cotton production in Xinjiang. The performance of such an irrigation system should be evaluated for proper design and management. Therefore, a field experiment and a simulation study were conducted to (1) determine a modeling approach that can be applied to manage drip irrigation under mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 37 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…For instance, the cumulative evaporation of soil moisture was lower in mulched soils than bare soils, and the reduction was related to mulch coverage and mass [16] [20].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the cumulative evaporation of soil moisture was lower in mulched soils than bare soils, and the reduction was related to mulch coverage and mass [16] [20].…”
Section: Introductionmentioning
confidence: 99%
“…The HYDRUS-2D model and the dual crop coefficient approach of FAO-56 were calibrated using the measured data in 2014, and produced a cumulative bias under the extreme rainfall conditions in 2013. Nevertheless, the simulated and measured results in 2013 still exhibited highly consistent trends, with several consecutive irrigation and precipitation events in the transplanted cotton growing seasons, particularly considering the complexity of the conditions to which the model was applied (i.e., heterogeneous soil properties, a more than 120-day simulation period, high evaporative demand, and assumed constant root distribution in one growth stage) [21,24].…”
Section: Modeling Soil Water Movement Under Different Irrigation Methodsmentioning
confidence: 82%
“…Overall, the changes in the simulated SWCs at 0-30 cm were more drastic than those at 30-90 cm in both irrigation treatments (Figures 11 and 12), since the 0-30 cm layer is more directly affected by irrigation, precipitation, evaporation, and transpiration [21,24]. The simulation results in Figures 11 and 12 showed that the HYDRUS-2D model overestimated the SWCs in July 2013.…”
Section: Modeling Soil Water Movement Under Different Irrigation Methodsmentioning
confidence: 92%
See 2 more Smart Citations